AN EXPLORATIVE AND COMPARATIVE ANALYSIS OF CONFIDENTIALITY PROCESSES IN WHISTLE-BLOWING MATTERS IN SOUTH AFRICAN WORKPLACES - Themba Mathebula; Momogau Mokgata (CV. RADJA PUBLIKA, 2024)
When a person decides to blow the whistle on wrongdoing in their workplace, they do so at great risk. This risk is not only posed to their employment but also to themselves and their loved ones as persons implicated often resort to retaliation. Therefore, whistle-blowers must be afforded maximum protection to cover all such risks. The Protected Disclosures Act (PDA) was enacted to protect whistle-blowers from retaliation. While the Act has been amended to include independent contractors and agents as some of the individuals who may receive protection, it does not provide for the concealment of the identity of the whistle-blower, or the information being disclosed. When no measures are taken to conceal the identity of the whistle-blower, they may be easily identified by the wrongdoer who may then ensue acts of retaliation. This research assesses the importance of confidentiality in whistle-blower protection. A comparative analysis is conducted to assess how some developed countries such as Canada, Australia and New Zealand have incorporated confidentiality in whistle-blower protection laws. This comparison allows some lessons to be drawn which can be adopted in South Africa to improve whistle-blower protection. In this research, it is therefore agreed that the lack of firm and reliable whistle-blower protection clauses in South African law, has devastating consequences for those who blow or intend to blow the whistle.